The MARES AUV, a Modular Autonomous Robot for Environment Sampling - Nuno A. Cruz (2008)
In this paper, we discuss the design aspects and the development of the MARES AUV, a 1.5m long vehicle, weighting 32kg, designed and built at the University of Porto, Portugal. This vehicle is highly maneuverable, with the ability to move in the vertical plane, controlling pitch and vertical velocity; forward velocity can also be determined, anywhere between 0 and 2 m/s. MARES can easily integrate any new payload within reason, finding applications in a wide range or areas, such as pollution monitoring, scientific data collection, sonar mapping, underwater video or mine countermeasures.